Strategi Pengembangan Sektor Pariwisata Kabupaten Banyumas - Aripradana Aripradana; Neni Widayaningsih (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2006)
This research is entitled “The Development Strategies of Tourism Sector in Banyumas Regency”. The aims of this research are to gain illustration of internal and external tourism sector’s condition and alternative strategies for the development of tourism sector in Banyumas Regency. The Strategy-formulation Analytical Framework is used to decided these alternative strategies, which divided into three stages; the input stage, the matching stage, and the decision stage. Each stage has different analysis methods. The first stage consists of the IFE matrix and the EFE matrix, the second stage is consists of the IE matrix and the SWOT matrix, whereas the third stage consist only one analysis method, that is the QSPM matrix. From the internal tourism sector’s condition analysis, it is found eight strengths and eight weaknesses factors in Banyumas Regency. In addition from the external tourism sector’s condition analysis, it is found nine opportunities and four threats factors. By using the IFE matrix analysis, it is scorred 3,7 and the EFE matrix analysis, it is scorred 3,3. The IE matrix is used to analysis all those total score and the result shows that the tourism sector in Banyumas Regency is in the first cell. It means that tourism sector in Banyumas Regency could applied growing and building strategies, included intensive strategies (market penetration, market development, and product development) or integrative strategies (backward integrated, forward integrated, and horizontal integrated). Based on the SWOT matrix analysis result, there are five SO strategies, four WO strategies, four ST strategies, and two WT strategies. The result of the QSPM matrix analysis shows that two strategies can be applied objectively. From those, the strategy that has the biggest total attractiveness score (TAS) is more sustainable to be applied.Keyword: IFE Matrix, EFE Matrix, IE Matrix, SWOT Matrix, QSPM Matrix